EDITORIAL - Martos Ramos, Jose Javier (Sustainable Multilingualism / Darnioji daugiakalbystė, 2024)
Dear Sustainable Multilingualism community, welcome to the twenty-fourth issue of Sustainable Multilingualism. In his book Sapiens. A Brief History of Humankind (2014), Yuval Noah Harari argues that fiction allows us not only to imagine things, but to do so collectively and, above all, flexibly – something unprecedented and characteristic of the human species. He claims that this is the very ability that has enabled Homo sapiens to dominate the world. It is widely accepted that human cooperation developed thanks to the mastery of language. Lorenzo (2008) highlights several features of language that have contributed to a more versatile and flexible way of communicating compared to other species. These include the ability to articulate utterances about both the past and the present, the capacity of minimal units of the linguistic system to generate further meanings, and the ability to discuss the characteristics of the language itself (as described by Hockett, 1958). Undoubtedly, language is the tool that makes possible a social organization tailored to complex and ever-changing needs. Without this resource, as we understand it in society, communication and the transmission of content would probably take place through a different code, with different relational implications. Communities have always adapted and shaped their language systems in different contexts (Brinker, 1997): private (such as personal relations within the family or circle of friends), official (such as relations with institutions), and public (such as relations through the media). Another form of adaptation is observed in communicative genres (Luckmann, 1986), which reflect how speakers construct routine and consolidated structures that provide more or less binding solutions to concrete communicative problems. Every language makes it possible to organize and regulate social relations in an acceptable way. It is therefore crucial to prioritize how language use is managed in order to adequately guarantee the rights and obligations of individuals. The Charter of Fundamental Rights of the European Union, proclaimed by the European Parliament, the Council, and the Commission in 2000, emphasises the right of citizens not to suffer linguistic discrimination and the importance of respecting linguistic diversity, as stated in its preamble and in Articles 21, 22 and 41. In the light of this objective, it is essential to legislate on language policy and planning in a Europe with more than 24 official languages, 60 languages spoken in regions or by specific groups, three different alphabets and a diverse immigrant population representing at least 175 nationalities (European Commission). These data paint a complex picture of language management, especially considering that languages are not governed by empirical parameters and should not be left alone (Wickström, Gazzola & Templin, 2018). The European Commission has consistently stressed the importance of language skills through measures such as the Common European Framework of Reference for Languages (2000) and the Erasmus+ mobility scheme (1987). It has also sought to promote multilingualism, recognized as one of the eight key competences necessary for personal fulfilment, through initiatives such as the recommendation to learn two foreign languages (Barcelona European Council, 2002) and the promotion of multilingual classrooms (2018). The impact of these measures can be seen in increased social awareness and higher rates of second language learning (Eurobarometer 386). However, despite these efforts, much remains to be done. The linguistic landscape in Europe shows a growing trend towards the use of English at the expense of other official and local languages. Everyday languages are gradually giving way to others that do not necessarily reflect the linguistic diversity of certain communities (see both Mazlum, Shadman & Khademnabi and Luchenko, Doronina & Chervinko in this volume). Examples include universities where technical degrees and masters are taught almost exclusively in English, even though English is not an official language. No government should neglect Europe’s linguistic and cultural diversity, as this would ignore the fundamental needs of its citizens. We need more tools to continue to defend values and rights as fundamental as linguistic ones (see Sabaliauskienė & Cortés Gañán in this volume). Political action must legislate and promote fair use according to local circumstances, even if economic parameters often dictate such measures (Wickström, Gazzola & Templin, 2018; Conceição, 2020). Certainly, economic factors cannot and should not be ignored in any society, but they must be balanced with the rights of citizens to express themselves in their own language, or at least in the language of the community in which they live. I would almost dare to compare this situation to that of city dwellers, whose habitual places are gradually being displaced by unsustainable tourism, forcing them to constantly adapt their habits. 2024 is an election year in Europe. Linguists and society in general will have to pay close attention to how the linguistic rights of the inhabitants of the European Union are managed. If we want a fairer Europe, we need a real promotion of multilingualism that goes beyond good intentions. We need policies that promote local and regional languages, while raising awareness of the value of language as a tool for cultural expression and management. For all the above reasons, it is to be welcomed that this issue of Sustainable Multlingualism addresses many of the aspects involved in developing and managing languages. Its first section "Society. Identity. Language Preservation and Revival" presents two studies touching on key aspects of identity and social language management. The first highlights the importance of heritage language proficiency for understanding cultural heritage, fostering identity development, and building social connections within both heritage and majority communities in a study of the heritage language of Korean American adolescents (Mi Yung Park). The second paper (Pittman & Glimois) discusses language management in multilingual family contexts and emphasizes the need to raise awareness among such families about the implementation of a Family Language Policy (FLP). Based on the reflections of two parents in multilingual families, the paper explores parental awareness of their family’s multilingual practices and policies, as well as strategies for supporting children’s language development. The findings point to the need for continuous updating of FLPs. In the second section, "Language use and education in multilingual and multicultural settings", four other articles focus on different learning situations. The first study (Luchenko, Doronina & Chervinko) examines the use of English as a medium of instruction (EMI) in the teaching of Japanese as a foreign language (JFL). It looks at the practices of JFL teachers from fifty-seven predominantly non-English-speaking countries and investigates the demographic, linguistic and contextual factors that influence their use of EMI. The results reveal several significant parameters, including teachers’ work experience, highest level of education, educational level, geographical region, native language group, Japanese language proficiency, and knowledge of other languages. A second study (B. Nangle, López Parreño, C. Nangle, Valūnaitė-Oleškevičienė & Gulbinskienė) analyses the most common English errors made by Lithuanian high school and university students in written tasks focusing on business and finance. The research suggests that detailed and personalized feedback can help to minimize errors in writing tasks, especially if it is accessible during the task. A third study examines the challenges of ESL learning in the context of autism spectrum disorders (ASD). As highlighted by the authors (Shaaban & Amr), there is a lack of research in an area that requires the involvement of parents, educational leaders and teachers. The study sample consisted of qualitative interviews with parents and teachers of children diagnosed with ASD. According to the findings of the research, teaching English as a second language to children with ASD using visual aids, modelling and repetition has been shown to be effective in improving the language and social skills of autistic children. The final study in this section (Ballıdağ & Dikilitaş) presents a case study of the bilingual Turkish-English education of a 5-year-old child using a ’non-native parent (NNP) strategy’ in a community where English is not the first or majority language. The results show that even limited exposure to a second language can lead to its acquisition through the NNP strategy and parents’ efforts to avoid code-mixing in their own discourse. In the third section on Romance languages, an article by Sabaliauskienė & Cortés Gañán aims to analyse the situation of foreign language teaching and learning at the Institute of Foreign Languages of Vytautas Magnus University (VMU). The study examines how the university’s language policy contributes to the EU’s goal of multilingualism. Key feedback from students suggests that there is room for improvement in the university system to promote multilingualism. Factors such as lack of awareness of the importance of languages, the increasing dominance of English, lack of motivation and negative learning experiences have a significant impact on the decline of interest in other foreign languages and pose a major threat to the implementation of multilingualism policies. In relation to the Spanish language, a second study (Serapinienė) focuses on formulaic language. Using the Sketch Engine software and a corpus from the EUR-Lex database, it was found that the grammatical meaning of these light verbal constructions is mostly represented by the supporting verbs tener, poner, dar, tomar and hacer. The final section, devoted to translation, presents two studies. The first (Mazlum, Shadman & Khademnabi) deals with the relationship between globalisation and translation. The authors argue that globalisation has led to an inexorable expansion of the English language around the world. Contrary to expectations, however, it has been found that, based on the opinions of Iranian translators, the need for translation services has not only not decreased but, on the contrary, has increased. Analysis of the data has revealed important factors in the Iranian context, namely the limitation of the target language (English) and the preference for Persian over English, as well as ideological issues. Finally, the second article in this section (Vaičenonienė) aims to answer the question of the distribution and translation into English of dual pronouns in Lithuanian fiction. It argues that dual pronouns, as a characteristic feature of the Lithuanian language, should be less common in translations. All in all, issue 24 of Sustainable Multilingualism brings together analysis and research on real-life evidence in which language plays a key role, impacting the people in the communities. Let’s enjoy all of them.